Citizens' Dialogues as a Contribution to Developing a European Public Space it's about Europe it's about YOU, join the debate - European Commission; European Parliament; European Economic and Social Committee; Committee of the Regions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2014)
As Europe is overcoming the financial and economic crisis, more and more decisions that have a direct impact on people's lives are taken at European level. This is therefore the moment to start a reflection on how to further strengthen the democratic structures of our Union. Before Europe implements the big reforms this will require, national and European politicians need to have a broad debate with citizens about what our future Europe should look like. This has to be a truly European debate, with citizens at its centre. That is why the European Commission has tested and developed a new communication tool to complement existing instruments that involve people directly: Citizens' Dialogues. The concept builds on the model of "town hall meetings" or local fora during which politicians listen to and debate with citizens about policies and decisions being taken. All in all, 51 Citizens' Dialogues have been held in all Member States. 22 out of 28 European Commissioners participated usually together with representatives of the European Parliament and national or local politicians (see table in the Annex). This gave the Citizens' Dialogues a real European dimension, which is enhanced by the fact that in many Member States, similar debates are now being organised at the national, regional and local level.
51 Citizens' Dialogues in 28 Member States September 2012 - March 2014.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Social surveys -- European Union countries; Europe -- Economic conditions -- 21st century; Electronic books